2016
DOI: 10.1111/ajt.13757
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific HLA Antibodies in Living Versus Deceased Donor Liver Transplant Recipients

Abstract: With less ischemia, improved donor selection and controlled procedures, living donor liver transplantation (LDLT) might lead to less HLA donor-specific antibody (DSA) formation or fewer adverse outcomes than deceased donor liver transplantation (DDLT). Using the multicenter A2ALL (Adult-to-Adult Living Donor Liver Transplantation Cohort Study) biorepository, we compared the incidence and outcomes of preformed and de novo DSAs between LDLT and DDLT. In total, 129 LDLT and 66 DDLT recipients were identified as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 30 publications
(46 reference statements)
4
48
1
1
Order By: Relevance
“…This suggests that while CNI therapy may participate in the clearance of pfDSA, these antibodies did not appear to have an impact on outcomes. Together, these results add to the controversy about pfDSA as some reports have shown associations with liver allograft failure and early rejection when pfDSA are against HLA‐II antigens …”
Section: Discussionmentioning
confidence: 60%
“…This suggests that while CNI therapy may participate in the clearance of pfDSA, these antibodies did not appear to have an impact on outcomes. Together, these results add to the controversy about pfDSA as some reports have shown associations with liver allograft failure and early rejection when pfDSA are against HLA‐II antigens …”
Section: Discussionmentioning
confidence: 60%
“…These corroborative findings, which are consistent with results in other organs, may help to explain recent data demonstrating higher survival and less impact of donor specific antibodies in LDLT vs. DDLT recipients. 5, 6, 23 In regard to immune-mediated diseases, higher rejection rates in autoimmune hepatitis have led to recommendations for augmented immunosuppression. 7, 15, 22, 24 However, in A2ALL and SRTR cohorts, LT recipients with other immune-mediated liver disease (primary biliary cirrhosis, primary sclerosing cholangitis) had significantly increased risks, suggesting the need to maintain a higher level of immunosuppression in all immune-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Levitsky et al . examined the association between DSAs and survival after DDLT and LDLT, and reported that preformed DSAs were associated with a higher graft failure rate only after DDLT . However, there was survival selection bias as the vast majority of the post‐transplant samples were available only at or after 3 months.…”
Section: Discussionmentioning
confidence: 99%